The impact of green credit policy on enterprises' financing behavior: Evidence from Chinese heavily-polluting listed companies. (20th August 2022) - Chai, Shanglei; Zhang, Ke; Wei, Wei; Ma, Wenyuan; Abedin, Mohammad Zoynul
Abstract: The enterprise's financing response to the green credit policy is of great significance. It is related to whether green finance can successfully accelerate enterprises' technological upgrading and transformation. Based on Propensity Score Matching-Difference in Difference (PSM-DID) model, this paper studies the impact of green credit policy on financing behavior of the heavily-polluting listed companies in China from 2008 to 2020. The results show that the illiquid debt financing behavior of heavily-polluting enterprises has a clear downward trend since China's "Green Credit Guidelines" were implemented, while liquid debt and commercial credit, as alternative financing methods for enterprises, have increased significantly. Through further analysis, we found that state-owned enterprises (SOE) are more affected by green credit policy than non-state-owned enterprises (NSOE), and companies in regions with a lower green development index are more affected by green credit policy than companies in higher green developing regions. Although China's green credit policy has a certain inhibitory effect on the illiquid debts financing behavior of heavily-polluting enterprises, it has failed to allocate the capital flow effectively due to the firm-level alternative financing response to the green credit policy. From the managerial significance of the policy, the signal guidance of green finance needs to be strengthened for enterprises. Graphical abstract: Image 1 Highlights: Explore the impact on financing behavior of green credit policy. Green credit policy is effective in reducing the illiquid debt of heavily-polluting enterprises. Green credit policy has led to an increase in alternative financing for enterprises. Explore the impact of green credit policies on different green development index regions.